Project appraisal in practice : the Little-Mirrlees method applied in Kenya - Scott, Maurice FitzGerald; MacArthur, J. D.; Newbery, David M. G. (London : Heinemann Educational Books, 1976)
This book attempts to show how the Little-Mirrlees method of shadow pricing can be applied in project evaluation in practice. Part 1 opens with a summary chapter which outlines the method and summarises the results. Part II is an economic appraisal of some of the land settlements in Kenya. Part III is a feasibility study of intensive cattle feeding.
Label mounted on t.p.: Holmes & Meier Publishers, Import Division, New York.
Includes index.
Includes bibliographical references: p. 535-540.
lje 03/10/2018
Loans
Keywords: Cost effectiveness; Land reform; Cattle trade; Kenya